Phase 3 Study of OnabotulinumtoxinA Distributed Between Frontalis, Glabellar Complex, and Lateral Canthal Areas for Treatment of Upper Facial Lines. Issue 11 (November 2018) - De Boulle, Koenraad; Werschler, William Philip; Gold, Michael H.; Bruce, Suzanne; Sattler, Gerhard; Ogilvie, Patricia; Street, James; Larsen, Kristin E.; Yushmanova, Irina; Lei, Xiaofang; Lee, Elisabeth; Vitarella, Domenico; et al.
Abstract : BACKGROUND: Although commonly practiced, simultaneous onabotulinumtoxinA injections to multiple facial areas have not been investigated in prospective studies. OBJECTIVE: Evaluate safety and efficacy of onabotulinumtoxinA for treatment of forehead lines (FHL) distributed between the frontalis (20 U) and glabellar complex (20 U), with or without simultaneous lateral canthal areas (crow's feet lines [CFL], 24 U) treatment. METHODS: Subjects with moderate to severe FHL were randomized (2:2:1) to onabotulinumtoxinA 40 U, onabotulinumtoxinA 64 U, or placebo. After 180 days, subjects could receive up to 2 additional open-label onabotulinumtoxinA 64 U treatments. RESULTS: The intent-to-treat (ITT) population comprised 787 subjects, and the modified ITT (mITT) population (subjects with psychological impact) comprised 568. After 30 days, onabotulinumtoxinA 40 U and 64 U significantly improved investigator- and subject-assessed FHL severity by at least 2 Facial Wrinkle Scale (FWS) grades in 45.6% and 53.0% of ITT subjects, respectively, versus 0.6% receiving placebo (both, p < .0001). Significantly more mITT subjects receiving onabotulinumtoxinA achieved investigator- and subject-assessed FWS ratings of none/mild versus placebo ( p < .0001). OnabotulinumtoxinA was well tolerated. CONCLUSION: OnabotulinumtoxinA distributed between the frontalis and glabellar complex, with or without additional CFL injections, was safe and effective for treatment of moderate to severe FHL.